2020
DOI: 10.3390/polym12040752
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Heterogeneity in Ring-Linear Polymer Blends

Abstract: We present results from a direct statistical analysis of long molecular dynamics (MD) trajectories for the orientational relaxation of individual ring molecules in blends with equivalent linear chains. Our analysis reveals a very broad distribution of ring relaxation times whose width increases with increasing ring/linear molecular length and increasing concentration of the blend in linear chains. Dynamic heterogeneity is also observed in the pure ring melts but to a lesser extent. The enhanced degree of dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
1
14
1
Order By: Relevance
“…In particular, the fraction of double-mode relaxation trajectories shows a maximum for ring-linear blends with 17% R-83% L composition and decreases upon further increases in ring fraction. A similar trend of heterogeneous relaxation of ring polymers was recently observed in ringlinear blend melts using MD simulations [69], where the distribution width of different relaxation modes for rings decreased with increasing ring composition in the blend. However, it is important to note that the heterogeneous relaxation behavior for rings observed here is qualitatively different than the relaxation of linear polymers in ultra-dilute solutions (10 −5 c * ) [42], linear polymers in semidilute solutions of purely linear chains [48,51], and ring polymers in ultra-dilute solutions (10 [52, 53], all of which exhibit a simple single-mode exponential decay for polymer relaxation in the terminal regime.…”
Section: A Longest Relaxation Time Of Ring Polymers In Ring-linear Bl...supporting
confidence: 83%
“…In particular, the fraction of double-mode relaxation trajectories shows a maximum for ring-linear blends with 17% R-83% L composition and decreases upon further increases in ring fraction. A similar trend of heterogeneous relaxation of ring polymers was recently observed in ringlinear blend melts using MD simulations [69], where the distribution width of different relaxation modes for rings decreased with increasing ring composition in the blend. However, it is important to note that the heterogeneous relaxation behavior for rings observed here is qualitatively different than the relaxation of linear polymers in ultra-dilute solutions (10 −5 c * ) [42], linear polymers in semidilute solutions of purely linear chains [48,51], and ring polymers in ultra-dilute solutions (10 [52, 53], all of which exhibit a simple single-mode exponential decay for polymer relaxation in the terminal regime.…”
Section: A Longest Relaxation Time Of Ring Polymers In Ring-linear Bl...supporting
confidence: 83%
“…We further examined the characteristic reorientation time of the rings, τ TACF . Following ref , we consider the generalization to circular chains of the time-lagged terminal autocorrelation function (TACF) of linear chains: C TACF false( τ false) = i , i + m / 2 false( t + τ false) · i , i + m / 2 false( t false) t , i where i , i + m / 2 is the normalized distance vector (diameter) of beads i and i + m /2; ⟨ ⟩ i , t indicates averaging over time and bead index i . C TACF thus measures the time-lagged orientational correlation of all diameters of the ring of interest.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Topological effects (threading) between a ring and a linear chain cause slow dynamics in ring–linear blends. Even for pure linear chains, slow dynamics occur owing to another topological effect (entanglement) that prevents chains from crossing each other. , Recently, the threading behavior of ring–linear polymer blends and the ring polymer melts has been extensively examined. From the experiments and simulations of ring–linear polymer melts under uniaxial elongational flow, it was found that the ring dynamics was strongly affected by the presence of even a few linear chains through threading.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, λ 1 /λ 3 and λ 2 /λ 3 ratios increased with the decreasing f ring . Mavrantzas et al studied the polymer melts of poly­(ethylene oxide) rings threaded with linear chains , and the dynamic heterogeneity of ring–linear blends . They found that the dynamics in ring–linear polymer blends is highly heterogeneous due to extensive threading where the linear chains dramatically obstructed the mobility of the rings.…”
Section: Introductionmentioning
confidence: 99%